Brain metastases from esophageal cancer: A retrospective analysis of the outcome after surgical resection followed by radiotherapy. Issue 34 (August 2019) - Stavrinou, Pantelis; Plambeck, Lars; Proescholdt, Martin; Ghadimi, Markus; Goldbrunner, Roland; Grau, Stefan
Abstract : Abstract: Brain metastases deriving from esophageal cancer are very rare with scarce data available concerning these patients' outcome. We, therefore, evaluated outcome after surgical resection followed by radiotherapy of brain metastasis from esophageal cancer. A retrospective analysis was conducted on consecutive patients undergoing resection of brain metastasis from esophageal cancer in 2 neuro-oncological centers between 2008 and 2018. Clinical and demographic data were retrieved from electronic patient charts. Post-treatment survival was calculated using Kaplan–Meier estimates. Twenty-five patients were identified. Treatment for primary disease comprised neo-adjuvant radio-chemotherapy followed by surgery (64.0%), surgery and adjuvant radio-chemotherapy (8.0%), radio-chemotherapy only (24.0%), and 1 patient receiving esophageal stenting only. Median time interval since initial diagnosis was 16 (range 0–110) months. All but 1 brain lesion were neurologically symptomatic and median Karnofsky performance score improved postoperatively from 70 to 80. After resection of brain metastases patients received whole-brain (n = 13 (52.0%)) or local fractionated (n = 9 (36.0%)) radiotherapy. In 2 patients adjuvant treatment was impeded by clinical deterioration; 1 patient refused radiotherapy. By the time of analysis 22 patients had died. Median survival after brain metastasis was 6 (95% CI 0.5–11.6) months. Survival after resection of metastasis from esophageal cancer is poor compared to other tumor entities. Nevertheless, resection of symptomatic brain metastases may improve clinical status in the context of a palliative concept.